Chemical Genomics Identifies the PERK-Mediated Unfolded Protein Stress Response as a Cellular Target for Influenza Virus Inhibition - Sara Landeras-Bueno (American Society for Microbiology, 2016)
ABSTRACT Influenza A viruses generate annual epidemics and occasional pandemics of respiratory disease with important consequences for human health and the economy. Therefore, a large effort has been devoted to the development of new anti-influenza virus drugs directed to viral targets, as well as to the identification of cellular targets amenable to anti-influenza virus therapy. Here we have addressed the identification of such potential cellular targets by screening collections of drugs approved for human use. We reasoned that screening with a green fluorescent protein-based recombinant replicon system would identify cellular targets involved in virus transcription/replication and/or gene expression and hence address an early stage of virus infection. By using such a strategy, we identified Montelukast (MK) as an inhibitor of virus multiplication. MK inhibited virus gene expression but did not alter viral RNA synthesis in vitro or viral RNA accumulation in vivo. The low selectivity index of MK prevented its use as an antiviral, but it was sufficient to identify a new cellular pathway suitable for anti-influenza virus intervention. By deep sequencing of RNA isolated from mock- and virus-infected human cells, treated with MK or left untreated, we showed that it stimulates the PERK-mediated unfolded protein stress response. The phosphorylation of PERK was partly inhibited in virus-infected cells but stimulated in MK-treated cells. Accordingly, pharmacological inhibition of PERK phosphorylation led to increased viral gene expression, while inhibition of PERK phosphatase reduced viral protein synthesis. These results suggest the PERK-mediated unfolded protein response as a potential cellular target to modulate influenza virus infection. IMPORTANCE Influenza A viruses are responsible for annual epidemics and occasional pandemics with important consequences for human health and the economy. The unfolded protein response is a defense mechanism fired by cells when the demand of protein synthesis and folding is excessive, for instance, during an acute virus infection. In this report, we show that influenza virus downregulates the unfolded protein response mediated by the PERK sensor, while Montelukast, a drug used to treat asthma in humans, specifically stimulated this response and downregulated viral protein synthesis and multiplication. Accordingly, we show that PERK phosphorylation was reduced in virus-infected cells and increased in cells treated with Montelukast. Hence, our studies suggest that modulation of the PERK-mediated unfolded protein response is a target for influenza virus inhibition.